2020
DOI: 10.1590/s1413-41522020178746
|View full text |Cite
|
Sign up to set email alerts
|

Evolução dos gastos públicos ambientais dos municípios brasileiros: uma análise no período de 2005 a 2015

Abstract: RESUMO O objetivo deste artigo consistiu em analisar os gastos públicos ambientais dos municípios brasileiros com população igual ou superior a 100 mil habitantes no período de 2005 a 2015. O gasto público ambiental municipal são despesas governamentais realizadas legalmente sob a forma de custeio, investimentos, transferências e inversões financeiras para cumprir as funções ambientais, consistindo na contabilização anual de cada município na função gestão ambiental (18) executada do orçamento municipal. Para … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…As already addressed, the program Maintenance of cleaning, collection and garbage processing activities of the PPA of Pato Branco, had the highest amount allocated, comprising 7.33% of the entire budget of the municipality (PATO BRANCO, 2017). In the research conducted by Guandalini, Borienelli and Godoy (2013) and Pereira and Figueiredo (2020) to assess environmental public spending between the periods 2002-2010 and 2005-2015 of Brazilian capitals and municipalities, it was found that these expenditures reached, on average, 1% of the total budget of the municipalities. In this context, the analysis performed in this research is very close to the values found by the authors.…”
Section: Joint Analysis Of Thementioning
confidence: 98%
“…As already addressed, the program Maintenance of cleaning, collection and garbage processing activities of the PPA of Pato Branco, had the highest amount allocated, comprising 7.33% of the entire budget of the municipality (PATO BRANCO, 2017). In the research conducted by Guandalini, Borienelli and Godoy (2013) and Pereira and Figueiredo (2020) to assess environmental public spending between the periods 2002-2010 and 2005-2015 of Brazilian capitals and municipalities, it was found that these expenditures reached, on average, 1% of the total budget of the municipalities. In this context, the analysis performed in this research is very close to the values found by the authors.…”
Section: Joint Analysis Of Thementioning
confidence: 98%
“…A partir da análise da literatura disponível tornou-se possível identificar as variáveis a serem analisadas neste trabalho, a saber: a. gastos municipais com gestão ambiental em valores absolutos (FARAGO; COELHO, 2018; PEREIRA; FIGUEIREDO NETO, 2018NETO, , 2020TRIPADALLI et al, 2011;WISSMANN et al, 2014) Os cálculos e análises realizadas consideraram tanto os valores absolutos quanto os respectivos valores per capita e percentuais de representatividade e de variação, tendo sido utilizada como base a Estatística Descritiva Univariada (média, mediana, quartis, curtose, assimetria, variância, desvio padrão e Coeficiente de Variação de Pearson, CVP). Os coeficientes de correlação de Pearson utilizados estão de acordo com Hair et al (2005, p. 312): ± 0,01 a ± 0,20 (leve, quase imperceptível); ± 0,21 a ± 0,40 (pequeno, mas definida); ± 0,41 a ± 0,60 (moderado); ± 0,61 a ± 0,80 (alta); e ± 0,81 a ± 1,00 (muito forte).…”
Section: Percurso Metodológicounclassified